Characteristics of air pollutants inside and outside a primary school classroom in Beijing and respiratory health impact on children. (December 2019) - Zhang, Lulu; Morisaki, Hiroshi; Wei, Yongjie; Li, Zhigang; Yang, Lu; Zhou, Quanyu; Zhang, Xuan; Xing, Wanli; Hu, Min; Shima, Masayuki; Toriba, Akira; Hayakawa, Kazuichi; et al.
Abstract: This study investigated the spatial and temporal distributions of particulate and gaseous air pollutants in a primary school in Beijing and assessed their health impact on the children. The results show that air quality inside the classroom was greatly affected by the input of outdoor pollutants; high levels of pollution were observed during both the heating and nonheating periods and indicate that indoor and outdoor air pollution posed a threat to the children's health. Traffic sources near the primary school were the main contributors to indoor and outdoor pollutants during both periods. Moreover, air quality in this primary school was affected by coal combustion and atmospheric reactions during the heating and nonheating periods, respectively. Based on the estimation by exposure-response functions and the weighting of indoor and outdoor pollutants during different periods, the levels of PM2.5, PM 10 and O3 at school had adverse respiratory health effects on children. Longer exposures during the nonheating period contributed to higher health risks. These results emphasized that emission sources nearby had a direct impact on air quality in school and children's respiratory health. Therefore, measures should be taken for double control on air pollution inside and outside the classroom to protect children from it. Graphical abstract: Image 1 Highlights: Air pollution inside and outside a primary school classroom in Beijing was serious. Sources nearby directly affected school's air quality and children's airway health. Indoor air quality was greatly affected by the input of outdoor pollutants. Health effects were estimated by weighting indoor and outdoor pollutants. The polluted air on campus increased the risk of respiratory health in children.